Media and the Issue of Hijab and Veil Across European Countries - Ab Halim, Asyiqin; Mohd Razif, Nor Fahimah; Paad, Nur Shahidah (Journal of Al-Tamaddun, 2022)
The issue of hijab has become a controversial and ongoing topic discussed mainly in European countries and has been perceived differently by the media. The discourse of hijab and its controversy, particularly in France, Netherland, Germany, as well as in the United Kingdom, has not been interpreted by the media according to the Islamic perspective, thereby implicitly creating tension between Muslims and the local society. Hence, the objective of this study is to examine the controversial issue of hijab that arose in the European countries by focusing on France, Netherland, Germany and the United Kingdom and how the issues have been reported and perceived by the media. This study employs a qualitative approach that applies library research focusing on data collection via secondary sources. Furthermore, the data are analysed according to thematic analysis in identifying and interpreting patterns and themes within the data obtained. The finding of this study shows the issue of hijab within European countries is regarding more on veil and purdah or niqab rather than headscarves as wearing of headscarves is commonly recognised by the European communities. As a conclusion, it is suggested for Muslims to be more visible in society and media in countering negative views and perceptions towards Muslim as well as in depicting constructive image of Islam.